Characterization of biological and metabolic responses to pH changes in a commensal Staphylococcus epidermidis strain - Santos, Susana Isabel Duarte dos (2019)
"Staphylococcus epidermidis is a Gram-positive commensal bacterium found mainly in mucous membranes but also in sebaceous areas. It is considered an opportunistic pathogen associated with nosocomial infections. Indeed, S. epidermidis is the main cause of coagulase negative staphylococci infections associated with medical devices. This thesis aims to understand the impact of pH conditions which mimic the skin pH (5.5) and blood pH (7.4) in a S. epidermidis commensal strain (19N) biological processes and metabolic pathways. Proteomic studies were realized by nanoscale liquid chromatography-tandem mass spectrometry (nano LC-MS/MS) and metabolomic studies through nuclear magnetic resonance (NMR) in the whole cellular extract."